Evidence of habitat specificity in sponge microbiomes from Antarctica - Maria F. Manrique-de-la-Cuba; Génesis Parada-Pozo; Susana Rodríguez-Marconi; Marileyxis R. López-Rodríguez; Sebastián Abades; Nicole Trefault (Environmental Microbiome)
Abstract Background Marine sponges and their microbiomes are ecosystem engineers distributed across the globe. However, most research has focused on tropical and temperate sponges, while polar regions like Antarctica have been largely neglected. Despite its harsh conditions and geographical isolation, Antarctica is densely populated by sponges. In this study, we explored the extent of habitat specificity in the diversity, community composition, and microbial co-occurrence within Antarctic sponge microbiomes, in comparison to those from other marine environments. We used massive sequencing of 16S rRNA genes and integrated multiple databases to incorporate Antarctic sponges as a habitat in global microbiome analyses. Results Our study revealed significant differences in microbial diversity and community composition between Antarctic and non-Antarctic sponges. We found that most microorganisms present in Antarctic sponges are unique to the South Shetland Islands. Nitrosomonas oligotropha, Candidatus Nitrosopumilus, Polaribacter, SAR116 clade, and Low Salinity Nitrite-Oxidizing Bacteria (LS-NOB) are microbial members characterizing the Antarctic sponge microbiomes. Based on their exclusivity and presence across different sponges worldwide, we identified habitat-specific and habitat-generalist bacteria associated with each habitat. They are particularly abundant and connected within all the Antarctic sponges, suggesting that they may play a crucial role as keystone species within these sponge ecosystems. Conclusions This study provides significant insights into the microbial diversity and community composition of sponges in Antarctica and non-Antarctic ecoregions. Our findings provide evidence for habitat-specific patterns that differentiate the microbiomes of Antarctic sponges from elsewhere, indicating the strong influence of environmental selection and dispersal limitation wrapped into the Antarctic ecoregions to shape more similar microbial communities in distantly related sponges. This study contributes to understanding signatures of microbial community assembly in the Antarctic sponges and has important implications for the ecology and evolution of these unique marine environments.